RETRACTION Rosidah, R., Setyawan, H., Mardiyah, S. U. K., Wisataone, V., Wolor, C. W., Sabariah, S., Rufi’i, R., Harmanto, H., Safrudin, S., Gontara , S. Y.., Arien, W., Susanto, S., & Eken, Özgür. (2024). Gestión de recursos humanos de profesores de Educación Física para alumnos con necesidades especiales en escuelas inclusivas. Retos, 61, 1495–1509. https://doi.org/10.47197/retos.v61.110181 - RETOS, RETOS (Retos, 2025)
Rosidah, R., Setyawan, H., Mardiyah, S. U. K., Wisataone, V., Wolor, C. W., Sabariah, S., Rufi’i, R., Harmanto, H., Safrudin, S., Gontara , S. Y.., Arien, W., Susanto, S., & Eken, Özgür. (2024).  Gestión de recursos humanos de profesores de Educación Física para alumnos con necesidades especiales en escuelas inclusivas. Retos, 61, 1495–1509. https://doi.org/10.47197/retos.v61.110181Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that the authorship of the article has been manipulated. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were needed. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. Likewise, a large number of citations and references were manipulated. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 3Authors in the published PDF with modified authors: 13Differences between the authors between both moments: +11 y -1 (Additions: Siti Umi Khayatun Mardiyah, Voettie Wisataone, Christian Wiradendi Wolor, Sabariah, Rufi’i, Harmanto, Safrudin, Satria Yudi Gontara, Wilasari Arien, Susanto, Özgür Eken. Eliminado: Zulbahri Zulbahri)